Flexible cross-linked polyester material as well as preparation method and application thereof
By blending vinyl-functionalized polyurethane with PPDO-PDLLA and radiocrosslinking them to form a three-dimensional network structure, the problems of insufficient flexibility and dimensional stability of PPDO-PDLLA material are solved, providing a safe and reliable high-end medical material solution.
Patent Information
- Application Number
- CN202511257605.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-04
- Publication Date
- 2025-12-09
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing PPDO-PDLLA materials have shortcomings in terms of flexibility, thermal responsiveness, and dimensional stability. Furthermore, traditional chemical crosslinking modification methods pose risks to biosafety and involve complex processes, making it difficult to meet the application requirements of high-end medical materials.
Flexible cross-linked polyester materials were prepared by blending vinyl-functionalized polyurethane with PPDO-PDLLA and forming a three-dimensional cross-linked network through radiation cross-linking technology, combined with a low-dose radiation cross-linking process.
It significantly improves the material's flexibility and thermoplasticity, enhances its ability to adhere to complex body surfaces, inhibits creep, maintains excellent shape and dimensional stability, meets medical material standards, reduces the risk of biotoxicity, and is suitable for the preparation of high-end medical materials.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_5
Abstract
Description
Technical Field
[0001] This invention relates to the field of biomedical polymer materials technology, specifically to a flexible cross-linked polyester material, its preparation method, and its applications. Background Technology
[0002] With advancements in medical technology, the demand for high-end medical materials in precision medicine, minimally invasive surgery, and personalized treatment is growing rapidly. These materials not only need excellent biocompatibility and biodegradability, but also must meet the requirements of specific application scenarios in terms of mechanical properties, flexibility, and environmental stability. For example, in applications such as soft tissue repair, absorbable sutures, and flexible drug delivery systems, materials need to possess both good mechanical support and conformal fit to match the dynamic mechanical environment of human tissues. However, the performance control of biodegradable polymer materials still faces many challenges.
[0003] Poly(p-dioxanone) (PPDO) materials have certain applications in medical devices, tissue engineering, and controlled drug release due to their good biocompatibility and biodegradability. However, PPDO has a high degree of crystallinity (typically >50%) and elastic modulus (typically >1.5 GPa), resulting in insufficient flexibility, making it difficult to meet the needs of applications requiring excellent compliance and fit, such as medical positioning, soft tissue scaffolds, and flexible drug delivery membranes.
[0004] Poly(racemic lactic acid) (PDLLA), an amorphous, biodegradable polymer, has a low glass transition temperature (approximately 50–60 °C) and good flexibility, and is commonly used in drug delivery systems and tissue engineering. However, PDLLA has low mechanical strength and is prone to softening and deformation under high temperature or humid conditions.
[0005] To address the aforementioned issues, we developed a copolymer of p-dioxanone and DL-lactide. The high molecular weight product PPDO-PDLLA, obtained by copolymerizing p-dioxanone and DL-lactide at a molar ratio of 70:30, has a melting point below 80°C. However, PPDO-PDLLA has a linear structure and lacks a cross-linking network, making it prone to creep or mechanical property degradation under long-term use or in humid environments. Existing chemical cross-linking modification methods, while improving flexibility, suffer from poor biocompatibility, weak controllability, and high residual toxicity risks due to the peroxide cross-linking agents used. Furthermore, the processes are complex and difficult to scale up.
[0006] Polyurethane (PU), a polymer material with excellent flexibility, elasticity, and biocompatibility, is widely used in flexible medical devices such as medical catheters and artificial blood vessels. However, significant technical challenges remain when attempting to use PU for the blending modification of PPDO-PDLLA: On the one hand, ordinary PU molecular chains lack crosslinkable active sites, making it difficult to form a stable three-dimensional network structure through radiation crosslinking, thus limiting its ability to improve the mechanical properties and dimensional stability of PPDO-PDLLA; on the other hand, the molecular structural differences between PU and PPDO-PDLLA lead to easy phase separation during blending, resulting in uneven material properties and making it difficult to achieve synergistic optimization of mechanical strength and flexibility, severely restricting its application potential in the field of high-end medical materials. Summary of the Invention
[0007] To overcome the shortcomings of existing PPDO-PDLLA materials in terms of flexibility, thermal responsiveness, and dimensional stability, this invention proposes a flexible cross-linked polyester material, its preparation method, and its applications.
[0008] The specific technical solution of the present invention is as follows: A method for preparing a flexible cross-linked polyester material includes the following steps: S1. Synthesis of polyurethane prepolymer: PPDO-PDLLA-diol polyol with a molecular weight of 500~2000 was mixed with diisocyanate and stirred thoroughly. Under the action of a catalyst, excess -NCO and -OH were reacted to obtain a polyurethane prepolymer with -NCO end groups. S2, chain extension reaction: A chain extender was added to carry out a chain extension reaction to obtain polyurethanes with -NCO end groups and a molecular weight of 700~4000. S3, Vinyl functionalization: Polyurethanes with -NCO end groups are reacted with hydroxyl-containing acrylate compounds to introduce vinyl functional groups with unsaturated double bonds, resulting in vinyl-functionalized polyurethanes with radiation-crosslinking capabilities. S4. The vinyl-functionalized polyurethane is blended and dispersed with PPDO-PDLLA with a molecular weight of 5000~200000 to obtain a blend: S5, Radiation crosslinking: By utilizing the double bond structure of vinyl-functionalized polyurethane, PPDO-PDLLA material is endowed with high radiation crosslinking sensitivity. The blend is subjected to irradiation crosslinking reaction in a non-toxic environment using electron beam, gamma ray, or ultraviolet light source to form a three-dimensional crosslinking network, resulting in a flexible crosslinked polyester material.
[0009] Preferably, the diisocyanate in step S1 is selected from one or a combination of at least two of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), and isophorone diisocyanate (IPDI).
[0010] Preferably, the reaction temperature in step S1 is 80°C and the reaction time is 1~3h.
[0011] Preferably, the chain extender in step S2 is selected from one or a combination of at least two of 1,4-butanediol, ethylene glycol, 1,3-propanediol, neopentyl glycol, and 1,6-hexanediol.
[0012] Preferably, in step S3, the molar ratio of NCO:OH in the polyurethane containing -NCO end groups to the hydroxyl-containing acrylate compound is 1:1.
[0013] Preferably, the hydroxyl-containing acrylate compound is selected from one or a combination of at least two of hydroxyethyl acrylate (HEA), hydroxypropyl acrylate (HPA), hydroxyethyl methacrylate (HEMA), and pentaerythritol triacrylate (PETA).
[0014] Preferably, the blending and dispersion method described in step S4 is specifically selected from one of the following methods: Method 1: Dissolve vinyl-functionalized polyurethane in chloroform or DMF, mix it with PPDO-PDLLA aqueous solution at a solute mass ratio of 1% to 10%, and evaporate the solvent to obtain a blend; Method 2: Using an internal mixer, vinyl functionalized polyurethane and PPDO-PDLLA are uniformly blended at 90°C at a mass ratio of 1% to 10% to obtain a blend.
[0015] Preferably, the irradiation dose in step S5 is 5~50 kGy.
[0016] The present invention also provides a flexible cross-linked polyester material, which is prepared by the above-described preparation method.
[0017] The present invention also provides an application of the above-mentioned flexible cross-linked polyester material, specifically for the preparation of medical positioning devices, drug controlled release carriers, soft tissue engineering scaffolds, flexible implants or smart medical materials.
[0018] Compared with the prior art, the specific beneficial effects of the present invention are as follows: This invention, through innovative material design and preparation process, successfully overcomes the shortcomings of traditional PPDO-PDLLA materials in terms of flexibility, thermal responsiveness, and dimensional stability, providing a novel material solution with excellent performance and high reliability for the field of high-end medical materials.
[0019] 1. The flexible cross-linked polyester material provided by this invention exhibits significantly improved performance. Specifically, through vinyl-functionalized polyurethane and radiation cross-linking technology, the material's elastic modulus is reduced to 100-170 MPa, while the elongation at break is increased to 200%-400%, significantly improving the material's flexibility and ability to adhere to complex body surfaces. The synergistic effect of the PU flexible segments and the three-dimensional cross-linked network enables the material to exhibit low surface viscosity and excellent thermoplasticity at 60-75℃, meeting the high-precision molding requirements for medical positioning and other applications. The cross-linked network structure effectively inhibits creep in the material during long-term use or in humid environments, maintaining excellent shape and dimensional stability. 2. This invention employs a low-dose (5~50kGy) radiation crosslinking process, avoiding the biotoxicity risks of traditional peroxide crosslinking agents. Cytotoxicity testing (MTT method) shows a cell viability rate >98%, meeting the ISO 10993 medical material standard. The vinyl functionalized PU synthesized using PPDO-PDLLA-diol as raw material significantly improves compatibility with high molecular weight PPDO-PDLLA, effectively reducing phase separation during the blending process. This invention provides two process routes: solution blending and internal mixer blending, which meet both the needs of precise laboratory preparation and the requirements of efficient industrial production.
[0020] 3. This invention improves mechanical properties while fully preserving the biodegradable characteristics of PPDO-PDLLA. All raw materials and processes comply with medical material standards, ensuring safety for clinical applications.
[0021] This invention has broad application prospects, combining the biodegradability of PPDO-PDLLA with the flexibility of PU, and is particularly suitable for the preparation of medical positioning devices, drug controlled release systems, soft tissue engineering scaffolds, flexible implants, and smart medical materials. Attached Figure Description
[0022] Figure 1 The 1H NMR spectrum of PPDO-PDLLA obtained in Example 1; Figure 2 The infrared spectrum of the flexible cross-linked PPDO-PDLLA obtained in Example 6 is shown. Detailed Implementation
[0023] To make the technical solutions of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. It should be noted that the following embodiments are only used to better understand the technical solutions of the present invention and should not be construed as limiting the present invention.
[0024] Example 1. 1020.9 g of p-dioxanone, 617.7 g of DL-lactide and 3.8 g of dodecyl alcohol were added to a 3000 mL three-necked flask, heated to 130 °C and stirred for 30 min. 0.5 g of stannous octoate was added to the flask and the temperature was maintained at 130 °C. After stirring continuously for 48 h, high molecular weight PPDO-PDLLA was obtained.
[0025] 200 g of dichloromethane was added to the flask to completely dissolve PPDO-PDLLA. The solution was then poured into ethanol for precipitation. After vacuum drying at 50 °C for 24 h, the purified polymer was obtained. The number-average molecular weight of PPDO-PDLLA was determined to be 82690 and the molecular weight distribution was 1.20 by gel permeation chromatography.
[0026] The 1H NMR spectrum of PPDO-PDLLA was measured as follows: Figure 1 As shown, in the spectrum, 4.12 ppm, 4.56 ppm and 4.62 ppm belong to the methylene group in the PPDO structural unit of the PPDO-PDLLA material, and 1.78 ppm and 5.45 ppm belong to the methyl and methine groups in the PDLLA structural unit of the PPDO-PDLLA material.
[0027] The structural formula is as follows: .
[0028] Example 2. 102.1 g of p-dioxanone, 61.8 g of DL-lactide and 10.8 g of ethylene glycol were added to a 500 mL three-necked flask, heated to 130 °C and stirred for 30 min. 0.05 g of stannous octoate was added to the flask and the temperature was maintained at 130 °C. After stirring continuously for 12 h, PPDO-PDLLA-diol was obtained.
[0029] The number-average molecular weight of PPDO-PDLLA, determined by gel permeation chromatography, was 1050, and its molecular weight distribution was 1.10. The structural formula is as follows: .
[0030] Example 3. 10.0 g of PPDO-PDLLA-diol and 3.4 g of hexamethylene diisocyanate (HDI) were weighed and reacted at 80 °C for 3 h with thorough stirring to synthesize a polyurethane prepolymer with -NCO end groups and an -NCO content of 6.3 wt%.
[0031] 0.6 g of 1,4-butanediol was added as a chain extender, and the reaction was continued for 1 h to obtain a polyurethane with -NCO end groups and a molecular weight of approximately 4200.
[0032] The prepolymer was reacted with 2.0 g of hydroxyethyl acrylate at a molar ratio of -NCO to -OH of 1:1 to introduce unsaturated double bonds, yielding vinyl-functionalized polyurethane A. The structural formula is as follows: .
[0033] Example 4. 10.0 g of PPDO-PDLLA-diol and 5.0 g of diphenylmethane diisocyanate (MDI) were weighed and reacted at 80 °C for 1 h with thorough stirring to synthesize a polyurethane prepolymer with -NCO end groups, the -NCO content being 5.6 wt%. 0.4 g of 1,4-butanediol was added as a chain extender, and the reaction was continued for 1 h to obtain a polyurethane with -NCO end groups and a molecular weight of approximately 4700. The prepolymer was reacted with 2.0 g of pentaerythritol triacrylate at a -NCO to -OH molar ratio of 1:1 to introduce unsaturated double bonds, yielding vinyl-functionalized polyurethane B. The structural formula is as follows: .
[0034] Example 5. The PPDO-PDLLA obtained in Example 1 was injection molded into a dumbbell-shaped sample and then irradiated with an electron beam at a dose of 10 kGy using an electron beam irradiation accelerator.
[0035] 2.0 g (w1) of the irradiated sample was weighed and placed in a ground-glass conical flask containing 25 mL of hexafluoroisopropanol. The sample was swollen in an oven at 25°C for 48 h, followed by extraction for 24 h. Finally, the sample was vacuum dried at 50°C to constant weight, and the weight of the apparatus was recorded as w2. According to the gel content formula Vc = w2 / w1 × 100%, the gel content was calculated to be 4%.
[0036] Example 6. 5g of the vinyl-functionalized polyurethane A prepared in Example 3 and 45g of the PPDO-PDLLA prepared in Example 1 were mixed to prepare a 5wt% hexafluoroisopropanol solution. The solution was poured into a polytetrafluoroethylene mold, and after the solvent evaporated, the material was irradiated with an electron beam at a dose of 10 kGy using an electron beam irradiation accelerator to obtain a flexible cross-linked PPDO-PDLLA material. Its infrared spectrum is shown in [reference needed]. Figure 2 It can be seen that after irradiation, at 1640 cm -1 The absorption peak of the unsaturated double bond disappeared.
[0037] Tests showed that the material has a gel content of 37%.
[0038] Example 7. 5g of vinyl-functionalized polyurethane A prepared in Example 3 and 45g of PPDO-PDLLA prepared in Example 1 were added to a mixer for solid-phase blending. After blending, the mixture was injection molded into dumbbell-shaped specimens. The material was then irradiated with an electron beam of 20 kGy using an electron beam irradiation accelerator to obtain flexible cross-linked PPDO-PDLLA material.
[0039] Tests showed that the material has a gel content of 46%.
[0040] Example 8. 5g of vinyl-functionalized polyurethane B prepared in Example 4 and 45g of PPDO-PDLLA prepared in Example 1 were mixed to prepare a 5wt% hexafluoroisopropanol solution. The solution was poured into a polytetrafluoroethylene mold, and after the solvent evaporated, the material was irradiated with an electron beam of 10 kGy using an electron beam irradiation accelerator to obtain a flexible cross-linked PPDO-PDLLA material.
[0041] Tests showed that the material has a gel content of 43%.
[0042] Example 9. 5g of vinyl-functionalized polyurethane B prepared in Example 4 and 45g of PPDO-PDLLA prepared in Example 1 were added to a mixer for solid-phase blending. After blending, the mixture was injection molded into dumbbell-shaped specimens. The material was then irradiated with an electron beam of 20 kGy using an electron beam irradiation accelerator to obtain flexible cross-linked PPDO-PDLLA material.
[0043] Tests showed that the material has a gel content of 46%.
[0044] Example of results. The materials obtained in Examples 4-9 were subjected to performance tests respectively: 1. The tests for elastic modulus, elongation at break, and tensile strength shall be conducted in accordance with GB / T 528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber".
[0045] 2. The gel content was tested according to ISO 10147:2011, "Determination of the degree of crosslinking in polymers and plastics". 3. Cell viability testing GBT16886.5-2017 Biological evaluation of medical devices Part 5: In vitro cytotoxicity test.
[0046] The test results are shown in the table below:
[0047] As can be seen, the gel content of pure PPDO-PDLLA after irradiation is only 4%, while the gel content increases by 9 to 11 times after blending modification, confirming the effectiveness of vinyl functionalization design. The cell viability of the blended modified materials is >98.9%, which meets the biosafety requirements of medical devices.
[0048] The test results above demonstrate that, while maintaining the biosafety of the material, this invention has successfully achieved a significant improvement in the flexibility and processing performance of PPDO-PDLLA material through innovative molecular design and process control, providing a superior material solution for medical applications.
[0049] Obviously, the above embodiments are merely illustrative examples for clear explanation and are not intended to limit the implementation. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively list all possible implementations here. However, obvious variations or modifications derived therefrom are still within the scope of protection of this invention.
Claims
1. A method for preparing a flexible cross-linked polyester material, characterized in that, Includes the following steps: S1. Synthesis of polyurethane prepolymer: PPDO-PDLLA-diol polyol with a molecular weight of 500~2000 was mixed with diisocyanate and stirred thoroughly to allow excess -NCO to react with -OH, thus obtaining a polyurethane prepolymer with -NCO end groups. S2, chain extension reaction: A chain extender was added to carry out a chain extension reaction to obtain polyurethanes with -NCO end groups and a molecular weight of 700~4000. S3, Vinyl functionalization: Polyurethanes containing -NCO end groups are reacted with hydroxyl-containing acrylate compounds to obtain vinyl-functionalized polyurethanes. S4. The vinyl-functionalized polyurethane is blended and dispersed with PPDO-PDLLA with a molecular weight of 5000~200000 to obtain a blend: S5, Radiation crosslinking: The blends are subjected to irradiation crosslinking reaction in a non-toxic environment using electron beams, gamma rays, or ultraviolet light sources to form a three-dimensional crosslinked network, resulting in a flexible crosslinked polyester material.
2. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, The diisocyanate mentioned in step S1 is selected from one or a combination of at least two of diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), hexamethylene diisocyanate (HDI), 4,4'-dicyclohexylmethane diisocyanate (HMDI), and isophorone diisocyanate (IPDI).
3. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, The reaction temperature in step S1 is 80℃, and the reaction time is 1~3h.
4. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, The chain extender mentioned in step S2 is selected from one or a combination of at least two of 1,4-butanediol, ethylene glycol, 1,3-propanediol, neopentyl glycol, and 1,6-hexanediol.
5. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, In step S3, the molar ratio of NCO:OH in the polyurethane containing -NCO end groups to the hydroxyl-containing acrylate compound is 1:
1.
6. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, The hydroxyl-containing acrylate compound is selected from one or a combination of at least two of the following: hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, and pentaerythritol triacrylate.
7. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, The blending and dispersion method described in step S4 is specifically selected from one of the following methods: Method 1: Dissolve vinyl-functionalized polyurethane in chloroform or DMF, mix it with PPDO-PDLLA aqueous solution at a solute mass ratio of 1% to 10%, and evaporate the solvent to obtain a blend; Method 2: Using an internal mixer, vinyl functionalized polyurethane and PPDO-PDLLA are uniformly blended at 90°C at a mass ratio of 1% to 10% to obtain a blend.
8. The method for preparing the flexible cross-linked polyester material according to claim 1, characterized in that, The irradiation dose in step S5 is 5~50 kGy.
9. A flexible cross-linked polyester material, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 8.
10. An application of the flexible cross-linked polyester material as described in claim 9, characterized in that, It can be used to prepare medical positioning devices, drug controlled release carriers, soft tissue engineering scaffolds, flexible implants or smart medical materials.